Concurrent and Selective Determination of Dopamine and Serotonin with Flexible WS2/Graphene/Polyimide Electrode Using Cold Plasma (Small 45/2021). Issue 45 (11th November 2021) - Kim, Hyeong‐U; Koyappayil, Aneesh; Seok, Hyunho; Aydin, Kubra; Kim, Changmin; Park, Kyu‐Young; Jeon, Nari; Kang, Woo Seok; Lee, Min‐Ho; Kim, Taesung
Abstract : Flexible Electrodes In article number 2102757, Min‐Ho Lee, Taesung Kim, and co‐workers demonstrate an innovative fabrication method for a bunch of flexible electrodes with a WS2 /graphene heterostructure on polyimide by using plasma‐enhanced chemical vapor deposition. The flexible biosensor enables selectively voltametric signals for dopamine and serotonin and is evaluated by using artificial cerebrospinal fluid.